Advances in Fine Structure Optimizations of Layered Transition‐Metal Oxide Cathodes for Potassium‐Ion Batteries. Issue 2 (20th November 2022) - Wang, Xuanpeng; Xiao, Zhitong; Han, Kang; Zhang, Xiao; Liu, Ziang; Yang, Chen; Meng, Jiashen; Li, Ming; Huang, Meng; Wei, Xiujuan; Mai, Liqiang
Abstract: Potassium‐ion batteries (PIBs) have attracted significant research interest in the context of driving the advancement of grid energy storage due to K's elemental abundance and high theoretical output voltage. The main challenge facing PIBs is to find suitable cathode materials with fast transport kinetics and stable framework structures to intercalate/de‐intercalate the large‐size K + . Among these candidates, transition‐metal layered oxides are have excellent potential and have been extensively exploited due to their stable skeleton structure, simple synthetic chemistry, and high working potential. Herein, the current research status and prospects of layered transition‐metal oxide cathodes are summarized, especially focussing on the fine structure optimization engineering and energy storage mechanism. In addition, a brief overview of the research on advanced characterization techniques for PIBs is introduced in detail. Finally, the main research directions and hot spots of new‐type transition‐metal layered oxide cathode are also predicted, in order to guide the future development of advanced PIBs. Abstract : Potassium‐ion batteries (PIBs) have attracted significant research interest in the context of driving the advancement of grid energy storage. Transition‐metal layered oxides have excellent potential and have been extensively exploited in PIBs. The current research status and prospects of layered transition‐metal oxide cathodes are systematically summarized. The main research directions of new‐type layered oxide cathode is expected to guide future development of advanced PIBs.